Estimation of Population Mean Using Calibrated Weights in Stratified Random Successive Sampling in Presence of Incomplete Data - G. N. Singh; M. K. Pandey; A. Bandyopadhyay; Mutum Zico Meetei; Abdullah A. Zaagan; Ali M. Mahnashi; Sanaa Al-Marzouki (Journal of Mathematics)
This article proposes a new sampling method to address challenges that often occur in estimation problems when mixed response and nonresponse patterns are observed. It introduces a range of estimators to mitigate the nonresponse effects in survey data. The properties of the proposed estimators are deeply analyzed, and calibrated weights for each stratum are derived. Numerical studies demonstrate the superiority of the proposed estimation approach over the standard conventional methods. Finally, recommendations are made to survey statisticians.